Period2 gene mutant mice show compromised insulin-mediated endothelial nitric oxide release and altered glucose homeostasis - Carvas, João M.; Vukolic, Ana; Yepuri, Gautham; Xiong, Yuyan; Popp, Katja; Schmutz, Isabelle; Chappuis, Sylvie; Albrecht, Urs; Ming, Xiu-Fen; Montani, Jean-Pierre; Yang, Zhihong (Frontiers in Physiology, 2012)
Period2 (Per2) is an important component of the circadian clock. Mutation of this gene is associated with vascular endothelial dysfunction and altered glucose metabolism. The aim of this study is to further characterize whole body glucose homeostasis and endothelial NO production in response to insulin in the mPer2Brdm1 mice. We show that mPer2Brdm1 mice exhibit compromised insulin receptor activation and Akt signaling in various tissues including liver, fat, heart, and aortas with a tissue-specific heterogeneous diurnal pattern, and decreased insulin-stimulated endothelial NO release in the aortas in both active and inactive phases of the animals. As compared to wild type mice, the mPer2Brdm1 mice reveal hyperinsulinemia, hypoglycemia with lower fasting hepatic glycogen content and glycogen synthase level, no difference in glucose tolerance and insulin tolerance. The mPer2Brdm1 mice do not show increased predisposition to obesity either on normal chow or high fat diet compared to wild type controls. Thus, mice with Per2 gene mutation show altered glucose homeostasis and compromised insulin-stimulated endothelial NO release, independently of obesity.